A Linear Temporal Increase in Thrombin Activity and Loss of Its Receptor in Mouse Brain following Ischemic Stroke - Bushi, Doron; Stein, Efrat Shavit; Golderman, Valery; Feingold, Ekaterina; Gera, Orna; Chapman, Joab; Tanne, David (Frontiers in Neurology, 2017)
Background Brain thrombin activity is increased following acute ischemic stroke and may play a pathogenic role through the protease activated receptor 1 (PAR1). In order to better assess these factors we obtained a novel detailed temporal and spatial profile of thrombin activity in a mouse model of permanent middle cerebral artery occlusion (pMCAo). Methods Thrombin activity was measured by fluorescence spectroscopy on coronal slices taken from the ipsilateral and contralateral hemispheres 2, 5 and 24 hours following pMCAo (n=5, 6, 5 mice respectively). Its spatial distribution was determined by punch samples taken from the ischemic core and penumbra and further confirmed using an enzyme histochemistry technique (n=4). Levels of PAR1 were determined using western blot. Results Two hours following pMCAo, thrombin activity in the stroke core was already significantly higher than the contralateral area (11±5 vs 2±1 mU/ml). At 5 and 24 hours, thrombin activity continued to rise linearly (r=0.998, p=0.001) and to expand in the ischemic hemisphere beyond the ischemic core reaching deleterious levels of 271±117 and 123±14 mU/ml (mean±SEM) in the basal ganglia core and ischemic cortex penumbra respectively. The peak elevation of thrombin activity in the ischemic core that was confirmed by fluorescence-histochemistry was in good correlation with the infarcts areas. PAR1 levels in the ischemic core decreased as stroke progressed and thrombin activity increased. Conclusions In conclusion, there is a time and space related increase in brain thrombin activity in acute ischemic stroke that is closely related to the progression of brain damage. These results may be useful in the development of therapeutic strategies for ischemic stroke that involve the thrombin-PAR1 pathway in-order to prevent secondary thrombin related brain damage.